Assessment of ground water quality in and around of Madhyabharat paper mills, Janjgir-Champa, C.G, India - Hait, Milan; Vaishnav, M M (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Water is the most abundant precious and essential compound to sustain the life on the earth. Analytical studies of some selected physicochemical parameter with metallic elements were made on the underground water bodies of Paper mills industrial areas Janjgir-Champa Chhattisgarh. Water samples were collected from four different selected spot in the month of Oct'2012 to Dec'2012. Temperature, pH, E.C, Turbidity, TDS and D.O were analyzed instantly at the sampling spot while T.S, TSS, TH, Total Alkalinity, BOD, COD, Cl−, F−,SO42−, NO3−, PO43−, Na, K, Ca, Mg, Fe, Cu, Zn, Mn and Phenol by the standard method as per IS procedure. The statistical parameters like mean, SD, SE, %CV and Correlation coefficient(r) and WQI were systematically calculated. Around 60% of these parameters were above the maximum permissible limit of IS: 10500 and WHO standard of drinking water. The elevated values of these parameters are of great concern to public health when the water from these bore wells are consumed by people without treatment. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->